2019
DOI: 10.1039/c9py00854c
|View full text |Cite
|
Sign up to set email alerts
|

The journey of self-healing and shape memory polyurethanes from bench to translational research

Abstract: In this critical review, we have enlisted a comprehensive summary of different approaches that have been used over the past decade to synthesize self-healing polyurethanes including “close then heal” and “shape memory assisted self-healing” concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 136 publications
1
37
0
Order By: Relevance
“…The sample can be healed with the healing efficiency of close to 100% in 6 h at 25 • C. Mended material exhibited properties equivalent to an undamaged sample (Figure 15). Polymeric materials possessing shape memory along with self-healing properties (dualfunctional) has attracted increasing interests of researchers [12,108,109]. Lai et al [96] demonstrated the effect of carboxylated hydrogen bonding and shape memory of the polymeric system to exhibit self-healing phenomena at body temperature.…”
Section: Self-healing Via Carboxylated-bonded Supramolecular Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample can be healed with the healing efficiency of close to 100% in 6 h at 25 • C. Mended material exhibited properties equivalent to an undamaged sample (Figure 15). Polymeric materials possessing shape memory along with self-healing properties (dualfunctional) has attracted increasing interests of researchers [12,108,109]. Lai et al [96] demonstrated the effect of carboxylated hydrogen bonding and shape memory of the polymeric system to exhibit self-healing phenomena at body temperature.…”
Section: Self-healing Via Carboxylated-bonded Supramolecular Interactionsmentioning
confidence: 99%
“…This is an expensive process in both cost and time. However, inspired by nature, self-healing materials are at the forefront of recent development [5][6][7][8][9][10][11][12], and a substantial amount of research work has been dedicated to developing self-healing coatings that can restore the fundamental properties of the material [13][14][15][16][17]. By virtue of self-healing abilities, substantial improvements can be brought towards extending the functional lifetime, consistency, efficiency, and safety of coating materials.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several publications have appeared that have focused on the development of materials with both self‐healing and shape memory behavior. For this purpose, reference should be made to relevant reviews describing such material combinations in polyesters, [ 32 ] polyurethanes, [ 33 ] hydrogels, [ 34 ] as well as in ionic [ 35 ] and coordination polymers. [ 36 ] Such materials are also known as multistimuli and multiresponsive polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐healing and shape memory polymers, and their combination, are a branch of advanced materials with smart performances that are gaining attention due to the prolonged material life and the ability to obtain the initial shape from a temporary shape, respectively. [ 2–5 ] The primary shape memory and self‐healing studies were conducted on polyurethane [ 6 ] and poly(ε‐caprolactone) systems. [ 7–9 ] However, over the years, the individual studies on only shape memory or self‐healing materials have been extended to a wide variety of polymers.…”
Section: Introductionmentioning
confidence: 99%